2011
DOI: 10.1111/j.1529-8817.2010.00953.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Ultrastructure and Three-Gene Phylogeny of the Genus Mallomonas (Synurophyceae)1

Abstract: The genus Mallomonas, a common and often abundant member of the planktic community in many freshwater habitats worldwide, consists of 180 species divided into 19 sections and 23 series. Classification of species is based largely on ultrastructural characteristics of the siliceous scales and bristles that collectively form a highly organized covering over the cell. However, the relative importance of the different siliceous features of the scales, such as the dome, V rib, and secondary structures, as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 23 publications
1
47
0
1
Order By: Relevance
“…The amplification of ITS rDNA was performed as described in Kynčlová et al (2010), using the primers Kn1.1 (5ʹ-CAA GGT TTC CGT AGG TGA ACC-3ʹ; Wee et al, 2001) and ITS4 (5ʹ-TCC TCC GCT TAT TGA TAT GC-3ʹ; White et al, 1990). Amplification of the rbcL marker was performed according to Jo et al (2011), using the primers rbcL_2F (5ʹ-AAA AGT GAC CGT TAT GAATC-3ʹ; Daugbjerg & Andersen, 1997) and rbcL_R3 (5ʹ-GTA ATA TCT TTC TTC CAT AAA TCT AA-3ʹ; Jo et al, 2011). The cox1 marker was amplified according to Boo et al (2010), using the primers F692 (5ʹ-TTG TDT GGT CAG TTT TAA TTA C-3ʹ) and R1433 (5ʹ-GGC ATA CCT GCW ARA CCT AA-3ʹ; Boo et al, 2010).…”
Section: Dna Extraction Pcr and Dna Sequencingmentioning
confidence: 99%
“…The amplification of ITS rDNA was performed as described in Kynčlová et al (2010), using the primers Kn1.1 (5ʹ-CAA GGT TTC CGT AGG TGA ACC-3ʹ; Wee et al, 2001) and ITS4 (5ʹ-TCC TCC GCT TAT TGA TAT GC-3ʹ; White et al, 1990). Amplification of the rbcL marker was performed according to Jo et al (2011), using the primers rbcL_2F (5ʹ-AAA AGT GAC CGT TAT GAATC-3ʹ; Daugbjerg & Andersen, 1997) and rbcL_R3 (5ʹ-GTA ATA TCT TTC TTC CAT AAA TCT AA-3ʹ; Jo et al, 2011). The cox1 marker was amplified according to Boo et al (2010), using the primers F692 (5ʹ-TTG TDT GGT CAG TTT TAA TTA C-3ʹ) and R1433 (5ʹ-GGC ATA CCT GCW ARA CCT AA-3ʹ; Boo et al, 2010).…”
Section: Dna Extraction Pcr and Dna Sequencingmentioning
confidence: 99%
“…synuroideus», обитающего в тропических и субтропических широтах, имеют более узкий загнутый край, лишенный перфораций, а поры базальной пластины окружены 5-6 гранулами (Hansen, 1996;Vigna, Siver, 2003;Siver, Lott, 2006;Gusev, 2013). Последний признак особенно важен в систематике рода Mallomonas M. Perty (Gusev, 2013;Jo et al, 2013) и странно, что до сих пор никто не обращал внимания на подобные различия у Chrysodidymus. К сожалению, в единственной работе, посвященной чешуйчатым золотистым водорослям Малайзии (Dürrschmidt, Croome, 1985), приводится только электронно-микроскопическая фотография всей колонии Ch.…”
Section: результаты и обсуждениеunclassified
“…In their monograph on Mallomonas, Asmund and Kristiansen (1986), and later Kristiansen (2002), considered species with scales that lacked domes and secondary structures, that had smooth and bifurcate bristles, and that had cells with two emergent flagella as ancestral. Mallomonas bangladeshica (Takahashi & Hayakawa) Nicholls diverged at the base of the clade lacking V-ribs, and M. insignis at the base of the clade with a V-rib (Jo et al, 2011. Based on a three-gene dataset, Jo et al (2011) demonstrated that Mallomonas is divided into two major clades based, in part, on the presence or absence of a V-rib and that this divergence occurred in the Early Cretaceous .…”
Section: E Taxonomic and Phylogenetic Considerationsmentioning
confidence: 99%